The Effect of Compressive Strength Paving Blocks Utilizing Polypropylene Plastic Waste - Vetryx, Vanessa Regina; Indriani, Andi Marini; Utomo, Gunaedy (CIVED, 2024)
Waste is a big problem for every country in the world, including cities. Currently, the city of Balikpapan is experiencing rapid economic and population growth, of course the growth also brings challenge in waste management, especially plastic waste. The type of plastic waste than we often encounter especially in coffe shops is Polypropylene (PP). In this research, pp type plastic waste is recycled as a substitute for cement in paving blocks with a composition of 30%, 40%, 50% to sand. The test conducted on this research is compressive strength. The purpose of this research is to determine the effect of PP plastic melt mixture on paving block mortar on increasing compressive strength. From the research results obtained the maximum compressive strength value for the composition of 50% Polypropylene : 50% sand with a compressive strength value of 11,83 Mpa. Similiarly, with the composotion of 40% Polypropylene : 40% sand, this value of is included in the quality D which can be used for parks according to SNI 03-0691-1996. While the 30% composition is not included in the quality.